Electrochemical Sensing of Luteolin from Straw Pyrolysis Carbon Prepared by Molten Salt Carbonization - Youluan Lu, Youluan Lu; Xinwei Mu, Xinwei Mu; Yaopeng Liu, Yaopeng Liu; Zhen Shi, Zhen Shi; Yin Zheng, Yin Zheng; Wensheng Huang and Fangming Lou, Wensheng Huang and Fangming Lou (Journal of the Chemical Society of Pakistan, 2022)
In order to well use waste biomass and realise the quantitative analysis of luteolin, the sorghum straw from the old broom was used to prepare biomass carbon material (CMS-PCSS) through the molten salt carbonization. Then the CMS-PCSS was characterised by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) Raman spectra (Raman), and N2 sorption analysis. In addition, the electrochemical performance of the CMS-PCSS based sensors was examined by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). Under the first-rank experimental conditions, the electrochemical sensor established with this material performed well in the quantitative analysis and actual sample detection of luteolin, the detection range of luteolin was 0.05~10.0 μmol/L, and the actual achievable minimum detection limit was 0.019 μmol/L.